Foresighted Leading Theoretical Thinking and Practice of China$1 (Bs Regional Economic Development /s - Chen, Yunxian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Under the conditions of market economy, the government is an independent economic entity, whose function is not only to provide services and handle public affairs, but also to coordinate, advance and lead economic development. The dual functions of regional government include providing service and administration at the micro-level on behalf of market economy on one hand and leading, regulating and promoting economic development at the macro-level on behalf of the central government on the other hand. Foresighted leading means giving free rein to the government, especially regional government, in economic guidance, regulation and early warning. It also means that the government is responsible for effectively allocating funds and gaining advantages using market rules, leveraging market forces and other means such as investment, price, taxation, law, and organizational, institutional and technological innovations to promote the scientific and sustainable development of the regional economy.
Introduction Foresighted Leading: Theoretical Innovations Based on the Economic Development in China -- The (3z(BNew Deal(3y (Bin Shunde: Foresighted Leading is Optimal Service -- Intelligent Foshan: the Road to Amalgamation of Industrialization, Urbanization and Internationalization via Informationalizaion -- The Road and Direction of Economically Demonstrative Regions in China -- Meeting the Press: Let the Light of Capital Shine over Industrial Highland -- Internet Government -- Chen Yunxian in the Media: Watch Before Walking -- Epilogue.s
Keywords: Economics; Development Economics; Economics/Management Science; Development Economics